ANTIMICROBIAL ACTIVITY OF BACTERIOCIN FROM INDIGENOUS Lactobacillus plantarum 2C12 AND ITS APPLICATION ON BEEF MEATBALL AS BIOPRESERVATIVE - Arief, I.I.; Jenie, B.S.L.; Suryati, T.; Ayuningtyas, G.; Fuziawan, A. (Diponegoro University, 2012)
One purpose of food preservation is to extend the shelf life of foods. Biological preservations canbe conducted by adding antimicrobial substances, such as bacteriocin produced by lactic acid bacteriaand has been characterized as biopreservatives. The aims of this research were to evaluate antimicrobialactivity of bacteriocin produced by indigenous lactic acid bacteria Lactobacillus plantarum 2C12isolated from local beef and to study the quality of beef meatball with 0.3% bacteriocin asbiopreservative at different storage times (0, 3, and 6 days) in cold temperature (4oC), compared to 0.3%nitrite and control (without preservative). The results showed that bacteriocin from L. plantarum 2C12could inhibit pathogenic bacteria such as Escherichia coli, Staphylococcus aureus and SalmonellaTyphimurium. Bacteriocin was effective as well as nitrite as biopreservatives of meatballs by inhibitingthe growth of total microbes and E. coli. The addition of bacteriocin did not lead the physical andnutritional changes in the meatballs. The quality of meatball with bacteriocin treatment conformed withIndonesia National Standard of meatball.